Peristilahan bahasa Melayu: satu kajian sikap (Jurnal Bahasa, 2006)
At present, the Malay language terminologies corpus shows that, an amount of649 568 terminology entries (not including 123 885 MABBIM terminologies) had been successfully produced. (Berita Peristilahan: 1998). Steps in formation of terminologies that can be found in the book Pedoman Umum Pembentukan Istilah Pembentukan Istilah Bahasa Melayu (DBP: 1992) demanded that terminologies should be initially formed from the main/general Malay language vocabulary itself, secondly the vocabulary from the same cluster with the Malay language, thirdly, the vocabulary from the foreign language especially from the English language source and fourthly, the vocabulary from the other languages. Nevertheless, the tendency of receiving whatever that had been served or proposed by the terminological planners would not be Ally accepted by the users of the terminologies. In the end, the users would be the one who will determine the terms they want to use. This paper will spread out 10 types of users language attitude towards termi-nologies that had been produced through the method suggested by the language planners. The findings will hopefully assist us in the efforts of building Malay language terminologies in future.